Management of Independent Village-Owned Enterprises (BUMDes) in the Context of Increasing Member Participation in Mootawa Village, Bone Raya District, Bone Bolango Regency - Prastika, Sri Yurike; Rachman, Ellys; Antu, Yahya (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the extent to which Village-Owned Enterprises (BUMDes) are managed independently in order to increase member participation in Mootawa Village, Bone Raya District, Bone Bolango Regency. The type of research used is descriptive using a qualitative approach method, which refers to 3 focus indicators, namely, facility indicators, member understanding and transparency. The research results show that: the management of independent village-owned enterprises (BUMDes) in order to increase member participation in Mootawa Village, Bone Raya District, Bone Bolango Regency is not optimal, this is due to inadequate facilities, minimal understanding of members and low levels of transparency which can hamper the process of Agency Management. Independent Village-Owned Enterprises (BUMDes) in Order to Increase Member Participation.